Visual Semiotics of a Transforming Creative Market: Decorative Diversity and Visual Branding in Pasar Santa, Jakarta - Dewi Intan Kurnia; Dwiana Azahra Putri; Mevanita Syah; Raffi Ahmad Ramadhan; Rifka Andrian Prasetya (Politeknik Siber Cerdika Internasional, 2026)
Background: Traditional markets face mounting pressure from modern retail expansion; however, limited studies have examined how localized decorative elements and visual branding strategies contribute to their resilience and identity formation in urban contexts. This gap is particularly relevant in the Indonesian context, where traditional markets are evolving into creative and community-oriented spaces. Objective: This study aims to explore the relationship between decorative diversity and visual branding in Pasar Santa, Jakarta, and to analyze how localized aesthetic expressions influence consumer perceptions and strengthen market distinctiveness. Methods: The research employs a qualitative case study design with a visual-semiotic analysis approach, grounded in Barthes’s denotation–connotation framework. Data were collected through systematic non-participant observation across six visits (March–April 2025) conducted on both weekdays and weekends, yielding more than 200 photographs documenting signage, stall facades, murals, typography, color schemes, and spatial layouts. Results: The findings reveal two dominant stall typologies: traditional stalls characterized by functional-utilitarian aesthetics and creative stalls featuring curated branding strategies. Creative stalls tend to cluster spatially, forming visually cohesive micro-environments. Cultural motifs—including batik patterns, wayang imagery, and regional typography—coexist with global design trends, producing a hybrid visual landscape. Visual elements also undergo temporal changes through seasonal decorations and thematic events. Conclusion: Effective visual branding strategies that incorporate cultural authenticity and community collaboration can strengthen the competitiveness of traditional markets. These strategies not only support economic sustainability but also contribute to urban placemaking by preserving local identity while adapting to contemporary commercial dynamics.